Agile Model for the Gradual and Short-Term Deployment of an Enterprise Architecture in the Financial Sector - Avalos-Varillas, Kevin (2024)
New technologies are being decisive in opening up the financial services market, historically stagnant, to new providers, which has generated a new competitive environment that is booming. Companies must adopt new organizational forms, optimize resources, establish policies, and best practices with clients, so organizations respond to these challenges through the practice of Enterprise Architecture. This methodology allows us to align processes, data, applications, and technological infrastructure with the strategic objectives of the organization. Despite the growing impact, ignorance means that only a small number of companies obtain a digital transformation. For this reason, it seeks to develop an agile model for a gradual deployment and in a short term in an effective manner, which is fully accessible to entities within the financial sector. The objectives include analyzing the current situation of the financial sector, designing the model for the enterprise architecture, validating the proposed agile model and developing a continuity plan for the investigation. A model based on the agile SAFe methodology and the TOGAF business architecture framework will be developed, whose objective is to provide agile results without sacrificing good management and control. In addition, it also seeks to provide an easily adaptable guide so that companies interested in the field can begin to undertake the use of agile methodologies.